A case of hydrocele of the canal of Nuck in a female adult: Diagnostic challenges and surgical approach - Pulavarti, Raviteja; Patra, G T; Sahoo, Nibedita; Vempati, Pranav; Bavurothu, Sharanya Kumar (Indian Journal of Case Reports, 2026)
Hydrocele of the canal of Nuck is an uncommon condition in females, resulting from a persistent processus vaginalis that allows fluid accumulation along the course of the round ligament. Although well recognized in males as a hydrocele of the spermatic cord, this entity is rarely encountered in adult females and is often overlooked in the differential diagnosis of inguinal swellings. We report the case of a 33-year-old woman presenting with a gradually enlarging, painful swelling in the right groin. Clinical examination revealed an irreducible, non-tender mass without cough impulse. Ultrasonography demonstrated a well-defined, cystic lesion superficial to the femoral vessels, consistent with a hydrocele. The patient underwent surgical excision under spinal anesthesia. Intraoperatively, a bluish cystic mass extending toward the labia majora was identified, aspirated, and completely excised along with separation from the round ligament. Histopathology confirmed a cystic lesion lined by cuboidal to flattened epithelium with mild chronic inflammation. Post-operative recovery was uneventful. This case highlights the clinical and radiological challenges in diagnosing canal of Nuck hydrocele and emphasizes the importance of considering it as a rare but relevant differential in adult females presenting with inguinal masses. Surgical excision remains the definitive treatment of choice.